Aplikasi Pelayanan Pada Kantor Kelurahan (Studi Kasus Kantor Kelurahan Minasa Upa Kota Makassar) - Haq, Nur Aksanul; Raharjo, Muh. Fajri; Olivya, Meylanie (Jurnal Teknologi Elekterika, 2022)
The Minasa Upa Village Office is a community service facility fulfilling population administration and licensing. Currently, the service applied is still carried out in a conventional way, which requires residents to come and queue at the village office to receive services. It is necessary to come to the village office to obtain information on the requirements for making a letter, to find out whether the submitted letter has been completed. Based on these problems, a system is needed to help services at the Minasa Upa Village Office be more practical and efficient. This study implemented an E-Government system that utilizes information technology in service. The e-Government implemented is in the form of an Android-based application designed using the Java programming language and firebase as a database service. The application design method used is the System Development Life Cycle (SDLC) with a waterfall approach. The system testing technique used is black box testing which consists of two stages, namely alpha and beta testing. The results indicate that the application is built according to the expected needs. This is proven through the tests that have been carried out. In addition, based on the questionnaire results, users stated that the interface of the application was easy to understand, with an average score of 86%.